Andrea Mantegna making art (history) - Campbell, Stephen J. (Stephen John) 1963-; Koering, J?er?emie (Chichester, West Sussex, UK ; Malden, MA Wiley Blackwell, 2015)
"Explores the Mantegna's potentially transformative impact on the study of the early Renaissance"-- Provided by publisher.
In Search of Mantegna's Poetics : An Introduction / Stephen J. Campbell and J?er?emie Koering -- Andrea Mantegna : Painting's Mediality / Klaus Kr?uger -- Signing Mantegna / Daniel Arasse -- Mantegna the Grammarian / Guillaume Cassegrain -- Changing Forms : Mantegna's Poietics in the Camera Picta / J?er?emie Koering -- Mantegna's Camera Picta: Visuality and Pathos / Stephen J. Campbell -- The Griffin's Gaze and the Mask of Medusa : Self-Referential Motifs in Andrea Mantegna's Trial of St James / Andreas Hauser -- Artifice and Stability in Late Mantegna / Andrea Bolland -- Mantegna's Fictive Bronze Judith and Dido : Beyond Exemplarity / Francis Fletcher -- A 'Pictorial Letter' to Giuseppe Fiocco / Roberto Longhi.
"Originally published as Volume 37, Issue 2 of Art History, except for A 'Pictorial Letter' to Giuseppe Fiocco by Roberto Longhi."
Prof. Jocelyn C. Pinzon (Recommending faculty) - Bookfair2017
Includes bibliographical references and index.
Keywords: Mantegna, Andrea -- 1431-1506 -- Criticism and interpretation; Art, Early Renaissance -- Italy; Art, Early Renaissance -- Historiography